GENE-61. TEMOZOLOMIDE-INDUCED MISMATCH REPAIR INSUFFICIENCY AND HYPERMETHYLATION OF MGMT PROMOTER WITH HYPERMUTATION IN MALIGNANT GLIOMAS - Saito, Kuniaki (Neuro Oncol, 2017)
INTRODUCTION: Temozolomide (TMZ) induces inactivation of the DNA mismatch repair (MMR) genes in glioma especially with methylated MGMT promoter and hence causes hypermutator phenotype at recurrence. Here we show molecular changes that occur during TMZ treatment in glioma patients and those impacts on prognosis. METHODS: We collected 67 glioma samples from 31 patients (21GBM, 5 grade III, 5 grade II) who recurred after TMZ treatment and performed mutation analysis by target sequencing using Ion AmpliSeq Cancer Hotspot Panel v2, expression analysis of MMR proteins (MLH1, MSH2, MSH6, and PMS2) by Western blotting/IHC, and MGMT methylation analysis by pyrosequencing. Then, prognosis according to molecular profile was compared. RESULTS: MMR expression decreased during treatment in more than 40% of the cases. In 80% of cases with initially MGMT methylated tumors, new mutations were acquired at recurrence in cancer-related genes including PTEN and SMAD4. Gain of mutation occurred in conjunction with MMR expression inactivation during the therapy or loss of MMR expression at initial tumors. MGMT methylation level of recurrent tumors with mutation gain elevated significantly compared to their initial tumors. MLH1 inactivation and MSH2 inactivation during TMZ therapy were prognosticators of prolonged overall and progression-free survival, respectively. The prognosis after recurrence did not differ significantly between the group with mutation gain and that without. CONCLUSIONS: TMZ therapy to MGMT methylated glioma causes MMR inactivation and might result in recurrence as hypermutator phenotype. Treatment must be optimized according to the molecular status to improve outcome of the malignant glioma.